2015
DOI: 10.1177/0963721414550709
|View full text |Cite
|
Sign up to set email alerts
|

Moral Character in Person Perception

Abstract: Understanding how people form impressions of others is a key goal of social cognition research. Past theories have posited that two fundamental dimensions-warmth and competence-underlie impression formation. However, these models conflate morality with warmth and fail to capture the full role that moral character plays in impression formation. An emerging perspective separates moral character (or morality) from warmth on both theoretical and empirical grounds. When morality is pitted against warmth, morality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
179
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(197 citation statements)
references
References 33 publications
16
179
2
Order By: Relevance
“…Our results further demonstrate the centrality of apparent competence and morality to social outcomes (29,39), and support the idea that sociability and morality are distinct components of social warmth (25,40). The conflicting effects of attractiveness on interest and good scientist judgments indicate that, although the stereotypical scientist may be an impartial truth seeker with limited personal appeal (23,31), people partly treat science communication as a form of entertainment, where emotional impact and aesthetic appeal are desirable qualities (41).…”
Section: Discussionsupporting
confidence: 73%
“…Our results further demonstrate the centrality of apparent competence and morality to social outcomes (29,39), and support the idea that sociability and morality are distinct components of social warmth (25,40). The conflicting effects of attractiveness on interest and good scientist judgments indicate that, although the stereotypical scientist may be an impartial truth seeker with limited personal appeal (23,31), people partly treat science communication as a form of entertainment, where emotional impact and aesthetic appeal are desirable qualities (41).…”
Section: Discussionsupporting
confidence: 73%
“…However, the other moral components may be similarly or more relevant when other target-groups are considered. For instance, it has been shown that determining whether someone is honest and trustworthy largely predicts responses towards a wide range of social targets (Brambilla & Leach, 2014; see also Goodwin, 2015). Thus, while moral purity is especially relevant for determining attitudes towards sexual minorities, community and autonomy concerns are highly relevant for other social targets, such racial groups (Haidt & Kesebir, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…If so, it raises the question of whether the communal-agentic distinction offers a more parsimonious explanation for gender differences in negotiator ethics than moral identity. On the other hand, recent work has begun to distinguish warmth and sociability from morality (Goodwin, 2015), suggesting the answer is not so straightforward. Future research should explore the overlap between moral and communal identities.…”
Section: Avenues For Future Researchmentioning
confidence: 99%